Conceptual questions of a teacher about the teaching and learning process of mathematics in basic education (Research, Society and Development, 2019)
Faced with the technological transformations of the contemporary world, countless researches in the area of mathematics education are developed in order to present new techniques and methods that are effective in the process of teaching and learning mathematics in basic education. This article aims to present suggestions and questions drawn from several works of my own, published in journals specialized in education whose central theme is related to the act of teaching and the act of learning mathematics, linked to mathematical knowledge and mathematical doing in basic education . Methodologically, the work is of a theoretical nature composed of a bibliographical research, since its composition was generated from the published works. The results of this research are extremely important to improve the process of teaching and learning mathematics in basic education. In view of this, it is expected that this work may contribute to and assist educators and researchers in the area of mathematics education, in order to strengthen the teaching and learning process of mathematics.